Evaluasi Kinerja Operasional dan Finansial Angkutan Penyeberangan di Pelabuhan Merak - Irawan, Dedy; Mardiaman, Mardiaman (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Merak Port is a port that serves ferry services from the Merak-Bakauheni crossing, located in Pulo Merak District, Cilegon City, Banten, Java Island. The port operates 24 hours with ships operating at least 30 units per day out of a total of 65 ships. So that cumulatively for effective ship operation by 46% for 1 year, the purpose of this study is to see the existing operational and financial performance by using profitability ratios namely net profit margin (NPM) and return on investment (ROI) with research methods using descriptive methods comparative and quantitative approach, the evaluation results show that operational performance based on the frequency of ship trips only reaches 77% or as many as 37,515 trips/year from the prevailing operating pattern of 48,960 trips/year, while the financial performance based on profitability ratios seen from the NPM value of 39% and ROI of 84% is greater than the condition of the operating pattern according to the pattern with an NPM value of 35% and ROI of 74% which means that the operating pattern according to the existing schedule is greater than the actual condition, but overall the profitability ratio is still above average or positive value.